2016
DOI: 10.1590/1806-9061-2015-0198
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of In-Ovo Injection of Propolis on Egg Hatchability and Starter Live Performance of Japanese Quails

Abstract: KeywordsIn-ovo feeding, propolis, hatching traits, quail.Submitted: August/2016 Approved: September/2016 ABSTRACT The purpose of this study was to determine the effects of in-ovo injection of a propolis water extract on hatchability, embryonic mortality, starter live performance, and livability of Japanese quails. In total, 500 fresh hatching eggs were randomly distributed into five treatment groups of 100 eggs per treatment with four replicates of 25 eggs each. On day 14 of incubation, eggs from group 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 43 publications
2
12
2
1
Order By: Relevance
“…Our study was contrary to the findings of Aygun (2016), which demonstrated that plant extracts of thyme and savory could improve immunity, but not the embryonic hatchability. Our results revealed both APS and live ND vaccine adjuvanted with APS appeared to significantly enhance hatchability; however, the live ND vaccine only did not change the hatchability when compared to Lymphocytes proliferation rate is an indicator of the status of cellular immunity (Zhao, Hu, Wang, Liu, & Guo, 2013), has been widely used to evaluate immunogenetic capability of an adjuvant.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study was contrary to the findings of Aygun (2016), which demonstrated that plant extracts of thyme and savory could improve immunity, but not the embryonic hatchability. Our results revealed both APS and live ND vaccine adjuvanted with APS appeared to significantly enhance hatchability; however, the live ND vaccine only did not change the hatchability when compared to Lymphocytes proliferation rate is an indicator of the status of cellular immunity (Zhao, Hu, Wang, Liu, & Guo, 2013), has been widely used to evaluate immunogenetic capability of an adjuvant.…”
Section: Discussioncontrasting
confidence: 99%
“…Adjuvants aiming to strengthen immune responses have been extensively exploited in vaccine schemes (Coffman, Sher, & Seder, 2010). For example, certain polysaccharides extracted from Chinese medicines used as vaccine adjuvants could effectively enhance vaccination efficacies (Aygun, 2016; Saki & Salary, 2015). In this study, we evaluated the effects of Astragalus polysaccharide (APS) as a ND vaccine adjuvant on the humoral and cellular immune responses in chicks through in ovo embryonic vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The increased DAP and EM percentages in the control group (untreated) may be due to increasing water loss percentage from the eggs leading to high DAP as well as EM because of dehydration. These results disagree with the findings of Aygun (2016) who found that the hatchability of fertile eggs and EM for eggs treated with distilled water and injected with 1, 2 and 3% propolis water extract were not affected. Also, the findings of Abuoghaba (2017) showed that the DAP, EM were not affected by ascorbic acid treatment or the interaction between incubation temperature and ascorbic acid treatment.…”
Section: Relative Water Loss Hatchability and Embryonic Mortalitycontrasting
confidence: 99%
“…This could be attributed to the role of BP in the reduction of adverse effects of high incubation temperature. These results agree with Aygun (2016) who stated that the chick body weight at hatching was not affected by the in ovo injection of 1, 2 and 3% propolis during the incubation period.…”
Section: Chick Quality Traits and Internal Organ Percentages Of Newlysupporting
confidence: 93%
“…The defence mechanisms like enzymes and natural antioxidants (Surai, ) protect the developing chick. The IOI of nutrients with antioxidant roles may help to overcome any limitation of inadequate egg nutrition and improve antioxidative status (Aygun, ).…”
Section: Introductionmentioning
confidence: 99%